(untitled) (Journal of Educational Sciences, 2024)
Education can be defined as a systematic process of achieving a goal through perseverance and patience. Currently, the education system is witnessing a paradigm shift from traditional teaching to digital inclusion methodology. The change will not only increase the capacity of teachers, but also increase the knowledge base of students so that they can excel in the international arena. Therefore, the developing technologies allow to educate the educated generation and to solve the tasks in the modern school. The introduction of computer education into the primary school curriculum is one way to solve these problems. In the article, we will focus on the programming section in the subject "Digital Literacy" in elementary school. In particular, we develop methods for designing programming tasks for elementary school students, and present the process and results of qualitative research. In order to determine the cognitive requirements of these tasks for elementary school students, what students consider difficult and what easy, we are looking for an effective methodology for programming education in elementary school. To achieve these goals, we need to identify simple cognitive operations in elementary programming, and on the basis of these actions, it is intended to be more competent in considering the level of complexity of programming tasks and to formulate the correct gradation sequence (gradation) of tasks, to develop programming skills and computational thinking of elementary school students. The experimental work was carried out on the basis of the primary educational organization “ADAN” in Shymkent and secondary school № 11 named after A. Navoi. Pupils of 1st and 3rd grades took part in the study. Keywords: Information educational environment, algorithm, linear algorithm, algorithmic thinking, computational thinking, teaching, digital literacy.